School Leadership in West Africa: Findings from a Systematic Literature Review. Issue 3 (1st October 2016) - Bush, Tony; Glover, Derek
ABSTRACT: The literature shows that leadership is the second most important factor influencing school and learner outcomes, including levels of literacy and numeracy, school leaving examination results, and progression to secondary and higher education. This article focuses on school leadership in West Africa, drawing on a systematic review of the academic and 'grey' literature, commissioned by UNESCO. The aim of the desk research was to ascertain the state of school leadership at all levels. The study shows that no West African countries provide specific preparation for school principals. It also shows that the predominant leadership style is managerial, with accountability to the hierarchy, within and beyond the school. The article concludes that specific development programmes should be provided for current and aspiring principals.